Pemanfaatan Kecerdasan Buatan (Ai) Dalam Meningkatkan Efesiensi Dan Pengembangan Usaha Mikro,Kecil Dan Menengah (Umkm) - Bunga Amira; Muhammad Irwan Padli Nasution (JURNAL RISET MANAJEMEN (JURMA), 2023)
Usaha Mikro, Kecil, dan Menengah (UMKM) play a crucial role in the global economy, but they often face challenges in terms of productivity and competitiveness, especially in today's digital era that requires UMKM to understand rapidly evolving information technology. This article discusses the utilization of Artificial Intelligence (AI) as a potential solution to assist UMKM in overcoming their challenges. AI can enhance operational efficiency, personalize customer experiences, drive product innovation, and improve financial analysis within UMKM. However, the integration of AI also presents challenges, including initial costs, training needs, data security, and legal uncertainties. This article provides an overview of the benefits and challenges of AI in the context of UMKM, as well as highlighting future prospects. Leveraging AI is the key to enhancing the growth and sustainability of UMKM in the complex digital era of the global economy.